COVID-19 and research in pediatric urology. Issue 4 (August 2021) - Harper, L.; Bagli, D.; Kaefer, M.; Kalfa, N.; Beckers, G.M.A.; Nieuwhof-Leppink, A.J.; Fossum, M.; Herbst, K.W.; ,
Summary: COVID-19 began in December 2019 then spread worldwide. Providers, including pediatric urologists, had to adapt their clinical processes, and many non-covid research activities were suspended. COVID-19 impacts how research is financed, performed, and published, and is itself the subject of intense research. We present current research and publications specifically related to the urinary tract and the pediatric population.